Enhancing Agility and Security for Small and Medium Businesses through Cloud Technologies - Koka, Hasini (International Journal of Computer Sciences and Engineering, 2025)
Cloud computing is a more current approach to managing long-term business needs. Cloud computing is conceivable thanks to the rapid advancements of the web and next-generation laptops. Cloud computing supports private businesses in several ways. Backs up and stays updated with company information, runs schedulers, and works on data sharing. Small organization owners need to get what they need in today's ever-changing business environment, whether on their PCs, tablets, or phones, in the workplace, in the field, or movement. Cloud computing allows customers to access information from any area with a web connection. Cloud logging targets private companies by leveling the playing field. It will enable them to access trending innovations used by large companies without significant out-of-pocket expenses. Independent businesses can store information, run applications, and train teams remotely, supporting productivity and eliminating IT costs. The benefits of the Cloud also offer adaptability, so organizations can change their resources according to their interests without putting too much effort into the foundations. Additionally, cloud phases provide information security and hardening, safeguarding critical business data. By adopting cloud computing, private companies gain adaptability, cost reserve funds, and greater efficiency, making them innovative enterprises for development. This paper will discuss how the Cloud has affected the small business industries.